Alat Peringatan Pelanggaran Physical Distancing Berbasis Raspberry Pi sebagai Upaya Preventif Penyebaran Covid-19 pada Era New Normal - Hilal Fahrul Hamam; Irwan Ardiansyah; Burhan Dwi Ardiandyah; Dira Tri Puspita; Nancy Febriani Taek; Ardy Seto Priambodo (ZETROEM, 2021)
The Covid-19 pandemic that hit Indonesia forced the Indonesian population to be ready with a new normal order. With this condition, it is hoped that the community can implement changes to the new order of life by implementing health protocols. But nowadays, people often violate health protocols, physical distancing, which is one form of prevention in the new normal era. The innovation of a Raspberry Pi-based tool designed to produce warnings for physical distancing violations is expected to minimize violations. The camera installed on the system will help detect the distance between two or more people and will give a warning to immediately carry out physical distancing if the measured distance is less than 1 meter. The purpose of writing this research is to design a system and concept of "Preventive Efforts for the Spread of Covid-19 Through a Raspberry Pi-Based Distance Monitoring System". The method of writing this article uses the concept of a literature study involving several studies and scientific findings in the form of secondary data from research results that have been published in scientific journals. From the results of the tests that have been carried out, it is known that the tool has succeeded in detecting physical distancing violations between two or more people. After the tool can detect a violation, the tool emits a warning sound to inform the violation that has occurred. From the result, it can be concluded that this system proposed can run well as expected.